Influence of the loading protocol and platform switching in two‐implant bar‐retained overdentures: 3‐year results from a randomized controlled equivalence clinical trial. Issue 1 (19th November 2021) - Enkling, Norbert; Kokoschka, Franziska; Schumacher, Daniel; Kraus, Dominik; Schimmel, Martin; Abou‐Ayash, Samir
Abstract: Objectives: To test the null hypothesis that vertical peri‐implant bone level alterations (ΔIBL) are equivalent in immediately (IL) and 3‐month post‐placement (DL) loaded implants in mandibular implant overdentures (IODs) on two implants. Materials and Methods: Thirty‐two patients receiving two interforaminal implants, one with a platform‐switched and one with a platform‐matching abutment were randomly assigned to the IL or DL group (allocation ratio 1:1). All implants were primarily splinted with chairside‐customized bars, converting the existing removable complete dentures to IODs. Standardized radiographs were recorded. The influence of the loading protocol (IL vs. DL), implant platform (platform switched vs. platform matching), implant site (43 vs. 33), participant age (≤65 vs. >65 years), and definition of baseline (implant placement vs. implant loading) were analyzed, applying linear regression analyses (α = 0.05). The equivalence range was [−0.4; 0.4]. Results: Three participants of the IL group were lost during follow‐up. The overall mean ΔIBL was −0.96 ± 0.89 mm. The ΔIBL was equivalent in terms of the implant platform and implant site but not in terms of participant age (in favor of more elderly participants) and the loading protocol. A significantly smaller ΔIBL was observed in the IL when the baseline was considered to be implant placement ( p  = .017), but not when it was considered to be implant loading ( p  = .084). Conclusion: Immediate loading of primary‐splinted implants in two‐implant bar‐retained overdentures, seems beneficial relative to loading 3 months post‐placement, with respect to ΔIBL. The ΔIBL were equivalent in terms of platform switching.